2015
DOI: 10.1007/s00894-015-2719-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alloying on oxidation and dissolution corrosion of the surface of γ-Fe(111): a DFT study

Abstract: Effects of alloying elements in popular steels on the oxidation and dissolution corrosion of the surface of γ-Fe(111) have been investigated by performing density functional theory calculations within the local density approximation. First, the segregation of alloying atoms as well as preferential adsorption sites for oxygen and water were carefully examined, and it was found that all of the alloying elements considered had a tendency to segregate to the surface, and that the most preferred adsorption sites we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 44 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…We explain the role of formal charges, geometry, and surface electronic and mechanical properties on the BEs. Such knowledge can then be used to predict the water interaction with a wide range of surfaces and has applications in electrocatalysis and electrochemistry, surface wetting, solid–water interfaces beyond TMs, solids corrosion, ,, biological systems, , etc. As a consequence of the material-independent scaling relations we find between the N and O 2p lone-pair species, such knowledge is transferrable to other molecules in this class.…”
Section: Introductionmentioning
confidence: 99%
“…We explain the role of formal charges, geometry, and surface electronic and mechanical properties on the BEs. Such knowledge can then be used to predict the water interaction with a wide range of surfaces and has applications in electrocatalysis and electrochemistry, surface wetting, solid–water interfaces beyond TMs, solids corrosion, ,, biological systems, , etc. As a consequence of the material-independent scaling relations we find between the N and O 2p lone-pair species, such knowledge is transferrable to other molecules in this class.…”
Section: Introductionmentioning
confidence: 99%
“…The difference between RDE and MEA is that the diffusion of the dissolved base metals in MEA is much slower than that in RDE, resulting in much slower dealloying kinetics. This insight parallels the technology on "stainless" alloys 46 , fills a knowledge gap between the structure and durability of alloy catalysts under fuel cell operating conditions while reducing Pt-content in the catalysts. The findings demonstrate a paradigm shift from the traditional perception of dealloying-induced phase segregation to the design and preparation of alloy catalysts that are commercially viable.…”
Section: Resultsmentioning
confidence: 66%
“…According to Fermi-Dirac function, a lower work function implies a lower corrosion potential. Han, et al, [139][140] calculated the work function associated with water adsorption on γ-Fe(111) surface with 10 different alloy elements, and found that most of the alloying elements-especially Cr, Mo, and Si, but not Ti and Nb-can mitigate dissolution corrosion of the γ-Fe substrate in an aqueous environment. They also found that when Cr combines with interstitial atoms, especially in 2Cr-N and 4Cr-C co-doped surfaces, it leads to a weakening of the surface corrosion resistance.…”
Section: Modeling Dissolution Of Metallic Materialsmentioning
confidence: 99%